Grid integration techniques of wind power plants - Chen, Yuning. (2009)
Wind is currently the most developed renewable energy technologies. One of the greater challenges in a wind turbine distribution power system is to control the output voltage at required level meanwhile tracking the maximum power output in the given condition that the speed of wind is changing all the time. Therefore the design of a power conditioning system needs to be carried out in order to achieve those requirements. Thus my main objective for this project is to design and build an effective voltage and power control systems. This system comprises of a diode rectifier and a Z-source, which is yet to be released in the market, is cascaded to a 3-phase voltage source inverter (dc-ac inverter system).